“I Might Need a Good Lawyer, Could Be Your Funeral, My Trial”: Global Clinical Legal Education and the Right to Counsel in Civil Commitment Cases - Michael L. Perlin (Washington University Journal of Law & Policy, 2008)
In Part I of this Essay, I will review developments in the United States, with special focus on the Montana case of In re Mental Health of K.G.F., without doubt the most comprehensive decision on the scope and meaning of the right to counsel in this context from any jurisdiction in the world. In Part II, I will survey an array of other jurisdictions (common law, civil law, and mixed) and consider the range of findings (from nations in which there is no counsel, to perfunctory-at-best counsel, to almost-adequate counsel). In Part III, I will consider other major legal, political, and social developments that might, it is hoped, illuminate these issues. In Part IV, I will examine these issues from the perspective of clinical legal education. In Part V, I will consider the impact of sanism and pretextuality on these developments. Finally, I will offer some modest conclusions.
Keywords: Clinical legal education; Access to justice; Right to counsel; Civil commitment; Mental disability law; Montana; In re Mental Health of K.G.F.; Sanism; Pretextuality; International; States